1980
DOI: 10.1111/j.1476-5381.1980.tb10970.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF VARIATION IN ENDOGENOUS LEVELS OF ASCORBIC ACID ON THE in vitro IMMUNOLOGICAL RELEASE OF HISTAMINE AND SLOW REACTING SUBSTANCE OF ANAPHYLAXIS FROM ACTIVELY SENSITIZED GUINEA‐PIG LUNG FRAGMENTS

Abstract: The in vitro immunological release of histamine and slow reacting substance of anaphylaxis (SRS‐A) from actively sensitized guinea‐pig lung fragments was greatly reduced when the animals were maintained on an ascorbic acid‐deficient diet. Excessive dietary levels of ascorbic acid did not increase mediator release above normal levels. Restoration of ascorbic acid in the diet of scorbutic guinea‐pigs restored in vitro immunological histamine to normal levels. Variation in dietary levels of ascorbic acid had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Thus, Krell et al(1976), Brink et a1 (1981), Saad & Burka (1983), Turner et al (1983) and Mansour & Daniel (1987) found no increase of responsiveness or sensitivity to agonists in sensitized tissues which is in contrast with the results from the present study. This discrepancy may be explicable in a number of ways such as the different animal species or strain used, the sensitization procedure (differences in the antigen and coadjuvant used, route of administration, time elapsed between sensitization and death of the animal, resensitization, challenge with antigen before testing the agonists), the additional supply of ascorbic acid in the diet of animals (Hitchcock 1980), the tissue preparation (type of strip mounted in the organ bath, presence or absence of intact epithelium, size of loading tension imposed to the tissue), and the type of recording (isometric vs isotonic, etc.) Notwithstanding, other authors The characteristics of the hyperresponsiveness observed in the present study closely resemble those reported for the reserpine-induced supersensitivity in rabbit aorta (Kalsner 1974) which has been associated with an enhanced ability of the tissue to retain and utilize calcium (Carrier & Hester 1976;Krishnamurty & Mukherjee 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Krell et al(1976), Brink et a1 (1981), Saad & Burka (1983), Turner et al (1983) and Mansour & Daniel (1987) found no increase of responsiveness or sensitivity to agonists in sensitized tissues which is in contrast with the results from the present study. This discrepancy may be explicable in a number of ways such as the different animal species or strain used, the sensitization procedure (differences in the antigen and coadjuvant used, route of administration, time elapsed between sensitization and death of the animal, resensitization, challenge with antigen before testing the agonists), the additional supply of ascorbic acid in the diet of animals (Hitchcock 1980), the tissue preparation (type of strip mounted in the organ bath, presence or absence of intact epithelium, size of loading tension imposed to the tissue), and the type of recording (isometric vs isotonic, etc.) Notwithstanding, other authors The characteristics of the hyperresponsiveness observed in the present study closely resemble those reported for the reserpine-induced supersensitivity in rabbit aorta (Kalsner 1974) which has been associated with an enhanced ability of the tissue to retain and utilize calcium (Carrier & Hester 1976;Krishnamurty & Mukherjee 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The control group was subjected to the same protocol but received only saline. The guinea-pigs were transported from the animal house to the laboratory at least two weeks before entering the sensitization or sham procedures, kept in individual cages under controlled conditions of light and temperature and with supplementary amount of ascorbic acid included in their diet, according to Hitchcock (1980), until killed.…”
Section: Isolated Preparations and Sensitization Proceduresmentioning
confidence: 99%
“…These diverging results may be attributed to differences in the experimental conditions, which are not uniform throughout the literature. Thus, the gender [20], the imm unization regimen [21] or the additional supply of ascorbic acid in the diet [8] may influence the re sponsiveness of the guinea pig airways. The discrepancies may be attributed, among other reasons, to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…The con trol group was subjected to the same protocol but re ceived only saline. The guinea pigs were transported from the animal house to the laboratory at least 2 weeks before entering the sensitization or sham procedures, kept in individual cages under con trolled conditions of light and temperature and with a supplementary amount of ascorbic acid included in their diet [8] until sacrifice.…”
Section: Methodsmentioning
confidence: 99%
“…The normal group was subjected to the same protocol but the animals did not receive the antigen. The guinea pigs received a supplementary amount of ascorbic acid in their diet until sacrifice (Hitchcock, 1980). This sensitization procedure generates immunoglobulin GI (IgG,) as the major homocytotrophic antibody mediating the immediate hypersensitivity response in this species (Regal, 1984).…”
Section: Sensitization Proceduresmentioning
confidence: 99%